Ultrafast, high-intensity laser material interaction in polycrystalline alumina transparent ceramics - Chong, Poh Yin; Wu, Xingzhong; Castillo, Gabriel R.; Garay, Javier. E. (Acta materialia, 2025)
High-intensity pulsed laser-material interaction involves various laser parameters and material properties that cause material modifications. This study investigates the laser-material interactions of single-crystal alumina (SCA) and transparent polycrystalline alumina (PCA) —two materials with similar composition (Al₂O₃) but distinct microstructures. Unlike SCA, PCA has grain boundaries, fundamentally altering its optical and mechanical properties. Single-shot ultrafast laser irradiations (λ=1030nm, τp=490fs) were conducted in the high-intensity regime (1012 W/cm2 to 1015 W/cm2), where extreme temperatures and pressures drive modifications such as melting, ablation, and fracture. While both materials show a sublinear power law dependence of ablation depth on laser intensity, PCA exhibits a lower energy dependency and shallower ablation depths. The differences are partially attributed to increased absorption in the PCA caused by point defect-electric defect groups. Surprisingly, PCA demonstrates fracture-like damage despite its higher indentation-induced fracture resistance. This is attributed to substantially different loading (pressure) application rates; indentation produces quasi-static loading whereas pulsed laser-induced damage occurs in a dynamic (shock) regime. Additionally, PCA has a comparable laser-induced damage threshold (LIDT) to SCA at high magnification and lower at lower magnification, reinforcing the role of microstructural effects in laser response. This is the first detailed study of ultrafast laser-induced modification in highly dense, fine-grained PCA. The findings should be useful for the development of ultrafast laser processing of transparent ceramics. [Display omitted]